Reflections on the principle of the social function of contracts - Martins-Costa, Judith (2005)
ACCORDING TO THE BRAZILIAN CIVIL CODE, WHICH CAME INTO FORCE ON 2003, THE FREEDOM OF CONTRACT IS EXPRESSLY LIMITED BY THE PRINCIPLE OF THE SOCIAL DESTINATION OF CONTRACT. THIS PAPER IDENTIFIES HOW THE FREEDOM OF CONTRACT WAS TRANSFORMED BY THIS RULE.